Cyber crime, security and digital intelligence - Johnson, Mark (Gower Publishing, 2013)
In Cyber Crime, Security and Digital Intelligence, his second book on high technology risks, Mark Johnson goes far beyond enumerating past cases and summarising the requirements of data protection law, payment card industry or ISO standards